Employment, Wages, and Alcohol Consumption in Russia: Evidence from Panel Data - Erdal Tekin (Institute for the Study of Labor (IZA), 2002)
This paper examines the effects of alcohol consumption on employment and wages for males and females in Russia. Both cross sectional and fixed-effects models are estimated utilizing data from the Russia Longitudinal Monitoring Survey. The results from the models that do not control for unobserved heterogeneity indicate that alcohol consumption has a positive impact on employment and wages. Further, there is some evidence in favor of an inverse U-shaped relationship between alcohol consumption and the labor market outcomes. Once the unobserved heterogeneity is controlled for using fixed effects, the positive association diminishes for the employment models for males and females. For the wage models, controlling for unobserved heterogeneity strengthens the positive impact of alcohol consumption both in significance and magnitude for males, while the reverse is true for females. However, the inverse U-shaped relationship obtained in cross-sectional models no longer exists. The results underline that unobserved heterogeneity plays an important role on the relationship between alcohol consumption and labor market behavior for both males and females. The findings are robust to model specifications and various alcohol consumption measures.
Keywords: J20; J10; 330; Employment; wages; alcohol consumption; Russia; Alkoholkonsum; Arbeitsproduktivität; Lohn; Erwerbsverlauf; Arbeitslosigkeit; Schätzung; Rußland